Heterocyclic Aromatic Amine Formation in Barbecued Sardines (Sardina pilchardus) and Atlantic Salmon (Salmo salar) - Costa, Mariana (2009)
The formation of heterocyclic aromatic amines (HAs) during barbecuing of sardines (Sardina pilchardus) and Atlantic salmon (Salmo salar) to various degrees of doneness and grilling conditions was evaluated by HPLC-diode array (DAD)/fluorescence (FLD) detection. Additionally, the influences of charcoal and electric heat sources on formation of HAs in grilled salmon were compared. With regard to sardine samples barbecued at 280-300 degrees C, "rare" samples produced nondetectable amounts of HAs, "medium" sardines presented IQ, MeIQx, PhIP, and A alpha C at levels of 1.9, 4.4, 3.3, and 2.0 ng/g, respectively, and "well done" sardines presented IQ, MeIQx, TrpP-1, Trp-P-2, PhIP, A alpha C, and MeA alpha C at levels of 0.9, 2.2, 1.8, 8.2, 6.5, 17.7, and 10.6 ng/g, respectively. Different qualitative and quantitative profiles of HAs were observed in sardine and salmon samples cooked under similar conditions of temperature and doneness. Levels of 13.3, 3.5, 1.13, and 3.18 ng/g were obtained, respectively, for PhIP, A alpha C, MeACLC, and Glu-P-1 in salmon samples barbecued at 280-300 degrees C. The contents of HAs were significantly higher in these samples than in salmon samples barbecued at 180-200 degrees C or in the electric device. However, MeIQx content (0.5 ng/g) was lower in salmon samples barbecued at 280-300 degrees C than in the other samples.